1997
DOI: 10.1159/000106650
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Month, Randomized, Placebo-Controlled Trial of Propentofylline (HWA 285) in Patients with Dementia According to DSM III-R

Abstract: Alzheimer''s disease (AD) and vascular dementia (VaD) share several features such as overactivation of microglial cells, damage induced by free radicals, glutamate and calcium overload. Propentofylline (HWA 285) has shown beneficial effects on all of these common elements, thus favouring its use in both subtypes of dementia. In a multinational, randomized, 12-month, double-blind, parallel-group study 260 out-patients with mild to moderate AD or VaD received 300 mg propentofylline (n = 129) or placebo (n = 131)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
“…ADLs were measured in 55 trials, using 12 measures. 27,28,33,37,41,45,46,49,51,52,54,55,57,59,61,63,64,66,68,77,78,81,[85][86][87][88][89][90]92,97,104,[106][107][108][110][111][112]114,115,118,119,[121][122][123][124][125]128,134,135,137,138,[142][143][144][145] Biological markers were measured in 51 trials using a variety of nine biological t...…”
Section: Published Trialsmentioning
confidence: 99%
“…These studies suggested that the treatment may be beneficial but the differences between patients receiving treatment and those given the placebo were small and often not statistically significant. Another drug which may be effective is propentofylline [24][25][26], which strongly inhibits the potentially neurotoxic actions of activated microglia (free radical formation and transformation into brain macrophages). This drug may inhibit the progressive neurodegenerative process in dementia; however, randomized, double-blind placebocontrolled trials are required to establish whether this drug is effective.…”
Section: Curative Treatmentmentioning
confidence: 99%
“…31 After 12 months, the total patient population showed statistically significant treatment differences in favour of THE CANADIAN JOURNAL OF NEUROLOGICAL SCIENCES…”
Section: Propentofyllinementioning
confidence: 98%